THE ROLE OF SECONDARY MEDICAL STAFF IN THE REHABILITATION PROCESSES OF DISABLED CHILDREN - Azizova Feruza Lyutpillaevna; Urazalieva Ilmira Ravkatovna; Tulyaganova Dildora Sagdullaevna; Sultanova Nafisa Sabirovna; Avezova Guloyim Sattarovna; Sagdullaeva Mafura Abdukarimovna; Okhunova MarkhaboTurdalievna; Yusupova Ziyoda Abdumajidovna (The Bioscan, 2024)
Rehabilitation is a broad set of interventions designed to optimize functioning and reduce disability in individuals with health conditions in interaction with their environment. It consisted of studying the activities of rehabilitation nurses in improving the quality of life of disabled children, developing recommendations aimed at improving the activities of secondary medical workers in rehabilitation processes. The city of Tashkent has the highest number of applications. According to the age indicator, the group of disabled children aged 1 to 4 years made up 49%. The level of satisfaction of parents with the work of the rehabilitation nurse was 83.1 percent. In 15% of cases, it was found that the nurse was not informed about the procedure before the procedure. It was found that the education of the patient’s family members is at a low level. The quality and quantity of training manuals created for rehabilitation nursing are insufficient. It requires adaptation of the system of education and training in this field to international standards.